Two-neutron transfer as a tool to study pairing correlations in nuclei. Issue 1 (1st September 2022) - Barioni, A.; Kaur, G.; Alcantara-Nunez, J.; Assunção, M.; Guimaraes, V.; Lara, A.L.; Lepine-Szily, A.; Lichtenthäler, R.; Linares, R.; Mendes, D.R.; Pires, K.C.C.; Santos, O.C.B.; et al.
Abstract: A feasibility study of two-neutron transfer reactions, using 12 C and 19 F targets, was performed. In this experiment, a 6 He beam at 20 MeV incident energy was delivered by the RIBRAS facility. The main goal of this work was to test the RIBRAS system, operated in a single-solenoid mode, to investigate ( 6 He, α ) reactions in light nuclei. The excitation function of the 14 C nucleus, populated by the 12 C( 6 He, α ) reaction, was extracted from the data. Evidence of nn -transfer reactions populating the ground state and the first 0 1 + state in 14 C were observed. However, the present spectrum might have contribution from other reaction channels such as the 6 He breakup. Future experiments with the RIBRAS dual-solenoid mode will improve the quality of the data by reducing a significant amount of background.